Study on level of awareness on eating disorder among undergraduate students of UiTM Melaka City Campus / Nurul ‘Azimahtul Hawa Roslan and Nurfarahin Mohd Ariffin - Roslan, Nurul ‘Azimahtul Hawa; Mohd Ariffin, Nurfarahin (Faculty of Administrative Science and Policy Studies, 2012)
Malaysian adolescents and teenagers are at risk of developing body image issues. When teenagers starts skipping meals frequently and/or disappears to the toilet after meals, this should be concerned. If they tried starving herself, it could be on the brink of eating disorder problems such as anorexia nervosa and bulimia. It is said that one in five adolescents is prone to eating disorders. This eating disorder issue is certainly present in our society as we do have cases of individuals or children who have problems with their eating. Eating disorders are illnesses that cause a person to adopt harmful eating habits. They are most common among teenage girls and women, and frequently occur along with other psychiatric disorders such as depression and anxiety disorders. These are behavioural problems brought on by a complex interplay of factors, which may include emotional and personality disorders, family pressures, a possible genetic or biologic susceptibility, and a culture in which there is an overabundance of food and an obsession with thinness. The purpose of the study is to determine the awareness and perception on eating disorder among undergraduate students of UiTM Melaka Campus. The attributes related to this study is level of awareness, knowledge on impacts as well as perception of undergraduate students of UiTM Melaka Campus towards eating disorder.